ANALYSIS OF THE PRACTICE OF REMOTE BANKING SERVICES IN THE BANKING SYSTEM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This scientific article comprehensively analyzes the introduction of remote banking services in the banking system, their practical application, economic efficiency and role in the transformation of banking activities. The author has extensively studied the theoretical foundations of remote banking services, their development trends in global and local financial markets, and the implementation of these services in the banking system of Uzbekistan. At the same time, he has deeply analyzed the advantages and disadvantages of services based on digital technologies - mobile banking, Internet banking, telegram bots and automated service channels. The study identified the attitude of bank customers to remote services, the intensity of their use of services, and the problems arising in this process. As a result of practical analyses, the opportunities for increasing the speed and transparency of operations, reducing banking costs, expanding the customer base, and strengthening financial inclusion through the development of remote banking services were scientifically substantiated. The article, based on comparison with world experience, also pays special attention to the obstacles to the introduction of remote services in the banking system of Uzbekistan, in particular, problems in the provision of information technology infrastructure, cybersecurity, and the legal and regulatory environment